Strategi Parental Control sebagai Praktik Komunikasi Keluarga dalam Menghadapi Kecanduan Game Online pada Remaja: Studi Kasus SMP di Makassar - Rezky Febrianti; Arianto Arianto; Muh Akbar (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The development of digital technology has introduced new challenges to family parenting, particularly in addressing online game addiction among junior high school adolescents. This study aims to analyze the parental control strategies implemented by parents and to explore family communication patterns in managing online game addiction. The research employed a qualitative approach using a collective case study in several junior high schools in Makassar. Data were collected through in-depth interviews and observations with parents of children aged 12–15 years. The findings reveal that effective parental control strategies include time restrictions, direct supervision, and content filtering. However, the success of these strategies is highly dependent on the quality of communication within the family. An authoritative approach that combines clear rules with open dialogue proves more successful in shaping healthy digital behavior than an authoritarian approach. The main challenges in applying these controls include parents’ limited digital literacy and time constraints. The study concludes that effective parental control depends not only on technical measures but also on the quality of emotional relationships and communication within the family. Therefore, the collaboration among parents, schools and communities is essential to establish an adaptive and sustainable digital parenting model.